A protocol for systematic review on global diversity of human immunodeficiency virus-1 subtypes - Bhatta, Mihir; Majumdar, Agniva; Sahoo, Srijan; Dutta, Shanta (Journal of Kathmandu Medical College, 2023)
Background: Human Immunodeficiency Virus (HIV)-1 subtypes are heterogeneously distributed around the world. Recent works on near full-length genome sequencing of HIV-1 shows increasing events of different recombinant variants and subtype C viruses. The active change in HIV-1 subtype distribution patterns initiate global challenges for diagnosis, treatment and antiretroviral (ARV) drug design.Objectives: Present study has been initiated to provide a summary of the current data on the HIV-1 subtype diversity and distribution by region.Methods: The data will be extracted through data extraction form as per Population, Intervention, Comparison, Outcomes and Study (PICOS) framework. Risk of bias and quality assessment will be performed with the help of Egger’s test and modified Newcastle - Ottawa Quality Assessment Scale respectively. The protocol registration number was International Prospective Register for Systematic Reviews (PROSPERO) number CRD42023400199.Results: The pattern of HIV-1 subtypes and Circulating Recombinant Form (CRF)/Unique Recombinant Form (URF) along with their geographical distribution around the world.Conclusion: The future systematic review, which will be generated from the present protocol, may provide evidence of the diversity of HIV-1 subtypes around the world. The present protocol might be handy to conduct a systemic review (and meta-analysis, if possible) on the global diversity of HIV-1 subtypes.